2001
DOI: 10.1007/s00464-001-8166-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing the occult contralateral inguinal hernia

Abstract: In this study, patients believed to have unilateral inguinal hernias had OCHs in 13% of cases when examined by TADL. The actual bilateral hernia incidence was 25%, with a 37% false-positive rate for preoperatively diagnosed bilateral hernias. The high rate of bilateral hernias reported by the TEP approach alone suggests that some OCH findings may be an artifact of the TEP dissection. However, failure to search for an OCH could result in up to 13% of patients subsequently requiring a second repair. Because some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…In that study, a 13% rate of contralateral hernias in patients believed to have unilateral inguinal hernias with overall 25% bilateral hernia rate was reported [8]. The Ferzli gioup retrospectively reviewed their results of TEP in 724 consecutive male hernia repairs and found an 11.2% rate of incipient contralateral defects [12].…”
Section: Discussionmentioning
confidence: 99%
“…In that study, a 13% rate of contralateral hernias in patients believed to have unilateral inguinal hernias with overall 25% bilateral hernia rate was reported [8]. The Ferzli gioup retrospectively reviewed their results of TEP in 724 consecutive male hernia repairs and found an 11.2% rate of incipient contralateral defects [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, four new contralateral hernias were detected during this study and four new contralateral hernias were referred from another institution and were successfully repaired via TEP after an original TEP. Sayad et al [16] and Koehler [8] reported the rate of occult contralateral hernias found during TEP repair as 11 and 13%, respectively. Thus, failure to search for them can result in as many as 13% of patients subsequently requiring a second repair.…”
Section: Discussionmentioning
confidence: 99%
“…The TAPP approach was, therefore, utilized to allow assessment of the attachment of the cyst to the round ligament, followed by complete dissection and removal. Through the transabdominal approach, we were also able to exclude a concurrent contralateral hernia, reported in 13% of patients presenting with suspected unilateral inguinal hernias [6].…”
Section: Discussionmentioning
confidence: 98%